2019
DOI: 10.1007/s11748-019-01274-5
|View full text |Cite
|
Sign up to set email alerts
|

Solitary fibrous tumor of the trachea: a case report

Abstract: We experienced a surgical case of a rare primary tracheal tumor. A 77-year-old woman visited a local clinic with chief complaints of coughing, wheezing, and discomfort in the throat. Computed tomography revealed a mass measuring approximately 1.5 cm in the mediastinal trachea, extending from the membranous portion of the trachea to the esophagus. Bronchofibroscopy showed a flat, smooth-surfaced, round mass arising from the membranous portion. Surgery was performed because of the possibility of airway obstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…SFT usually interests adults between 20 and 70 years, indifferently male and female. This tumor grows slowly not determining pain, it can be associated with symptoms of compression, sometimes however its behavior is unforeseeable (9)(10)(11). SFTs show no specific tumor-oriented symptoms.…”
Section: What Is the Implication And What Should Change Now?mentioning
confidence: 99%
“…SFT usually interests adults between 20 and 70 years, indifferently male and female. This tumor grows slowly not determining pain, it can be associated with symptoms of compression, sometimes however its behavior is unforeseeable (9)(10)(11). SFTs show no specific tumor-oriented symptoms.…”
Section: What Is the Implication And What Should Change Now?mentioning
confidence: 99%
“…A few studies showed that pelvic [27,30,41], abdominal [27,42], and pleural [27,40,43] SFTs tend to be larger than tumors appearing in other locations, and extrapleural SFTs may show potentially malignant behavior [44], especially those with limb localization [45]. Generally, over the years, SFTs have been described in various localizations, including the liver [46,47], kidney [48][49][50], pancreas [23,51,52], sigmoid colon [31], mesocolon [14], omentum [53,54], urinary bladder [55], caecum wall [56], mesorectum [41], prostate [57], spermatic cord [58], testis [59], scrotum [60], female gynecological tract, especially the vulva [61,62], vagina [63], breast [64][65][66], heart and pericardium [33,67,68], epicardium [69], pulmonary artery [70], trachea [71], larynx [32,72], tongue [15], salivary glands [73]<...…”
Section: Anatomical Locationmentioning
confidence: 99%